Academic Library in Transition from Library as a Place to Library as a Learning Centre: A Case Study of Indian Institutes of Management - Kumar, Bharat (DESIDOC Journal of Library & Information Technology, 2015)
This paper is based on a study conducted in seven Indian Institute of Management (IIM) libraries, viz., IIM-Ahmadabad, IIM-Bombay, IIM-Calcutta, IIM-Indore, IIM-Kozikode, IIM-Lucknow, and IIM-Shilong. It discusses in detail the comparative status of the resources, implementation of IT, viz., software being used to automate library functions and provide remote access to library. Decreasing reliance on local collections is transforming the library as a physical destination. It also discusses about different information products and services provided by the libraries to their users to convert them as a learning centres.